Effectiveness Diabetes Self-Management Education (DSME) to Foot Care Behaviour and Foot Condition in Diabetes Mellitus Patient - Frisca, Sanny (KnE Life Sciences, 2021)
Diabetes mellitus (DM) is disease with hyperglycaemic condition. Hyperglycaemic can induce vascular problem (microvascular and macro vascular), neuropathy, and nephropathy. Microvascular and neuropathy can induce foot problem in patient, which can make amputation, increase medical cost, and care cost. Diabetes Self-Management and Education (DSME) can influence patient foot care behaviour and also patient foot condition. This research aim is to find effectiveness of DSME to patient foot care behaviour and patient foot condition. This research involve 112 respondents (intervention group= 56 respondents, control group= 56 respondents) with quasi experiment nonequivalent control group pre-test – post-test method. Intervention DSME was given for eight week with 15 minutes education every week for each patient, data collected by foot behaviour questionnaire and checking patient’s foot condition. In first week researcher collected pre-test data and in eight week researcher collect post-test data. Data analysed by ordinal regression at 5% for significant value. Result: DSME significantly increase foot care behaviour (p = 0.000) and influence foot behaviour 12.2%, DSME also significantly increase patient foot condition (p = 0.000) and influence foot condition 7.4%. DSME which applied with continuity can enhance foot care behaviour and awareness to checking foot condition then patient can avoid foot problem related to DM. Future research can use monofilament and Ankle Brachial Index for examination foot condition. Keywords: DSME, foot care behaviour, foot condition